Development of regional mixed-effects height–diameter models for natural black pine stands - Ramazan Ozçelik; Onur Alkan (Turkish Journal of Forestry)
In this study, linear mixed-effects height-diameter models were developed for natural black pine (Pinus nigra J. F. Arnold.) stands in the Isparta-Eğirdir region. Data collected from 135 sample plots between 2021 and 2022, consisting of 4,271 sample trees, were used for parameter estimation and calibration testing. The mean diameter and height in the model development group were 34.35 cm and 15.40 m, respectively, while in the test group, these values were 31.26 cm and 14.07 m. Various calibration alternatives, utilizing 1 to 10 trees, were tested to improve prediction performance. The results showed significant improvements in prediction accuracy of the models, especially with calibrations involving 5 or 10 trees. Compared to the fixed-effects model, the mixed-effects model achieved a 32% reduction in the root mean square error (RMSE). The findings suggest that the proposed model is highly suitable for forest inventory studies to predict tree heights in black pine stands.